Notes on four naturalized weeds in Morocco: extended distribution and new record - Tanji, Abbes; Khamar, Hamid (UMA Editorial, 2025)
This contribution deals with the record of four alien naturalized plants in Morocco due to field surveys conducted in 2023 and 2024, with special emphasis on weeds occurring in farmlands (agricultural regions of Chaouia, Gharb, Haouz, Loukkos, Sous, and Tadla). Among these reported plants, three are here presented as new national distributional records namely, Euphorbia heterophylla L., E. nutans Lag. (Euphorbiaceae) and Malvastrum coromandelianum (L.) Garcke subsp. coromandelianum (Malvaceae) whereas Cardiospermum microcarpum (Kunth) Blume (Sapindaceae) is here reported for the first time in the country. Photographic evidence, distribution map, and taxonomic notes are provided for each taxon. In addition, voucher herbarium specimens were prepared and deposited at the national herbarium of the Scientific Institute in Rabat (RAB)

Esta contribución trata del registro de cuatro plantas exóticas naturalizadas en Marruecos gracias a estudios de campo realizados en 2023 y 2024, con especial énfasis en las malezas presentes en las tierras de cultivo (regiones agrícolas de Chaouia, Gharb, Haouz, Loukkos, Sous y Tadla). Tres especies se reportan como nuevos registros de distribución nacional: Euphorbia heterophylla L., E. nutans Lag. (Euphorbiaceae) y Malvastrum coromandelianum (L.) Garcke subsp. coromandelianum (Malvaceae); en tanto que Cardiospermum microcarpum (Kunth) Blume (Sapindaceae) se registra por primera vez para el país. Se proporcionan evidencias fotográficas, mapas de distribución y notas taxonómicas para cada taxón. Además, se prepararon ejemplares de herbario de referencia, que se depositaron en el herbario nacional (RAB) del Instituto Científico de Rabat.
Notas sobre cuatro hierbas naturalizadas en Marruecos: distribución extendida y nueva cita
Keywords: Plantas exóticas - Marruecos; Fitogeografía; Plantas - Clasificación; Xenófitas; Estudio de malezas; Nuevos registros; Florística; Norte de África